2005
DOI: 10.1029/2005gl024298
|View full text |Cite
|
Sign up to set email alerts
|

Planetary wave coupling from the stratosphere to the thermosphere during the 2002 Southern Hemisphere pre‐stratwarm period

Abstract: Temperature observations between 20 and 120 km from the SABER instrument on the TIMED spacecraft are used to investigate the nature of planetary wave activity during the 60 days prior to the midwinter stratospheric warming that commenced on 26 September, 2002 in the Southern Hemisphere. The primary wave components consist of eastward‐propagating quasi‐10‐day waves with zonal wave numbers s = 1 and s = 2, and a stationary planetary wave with s = 1. The waves are found to extend from the lower stratosphere to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 18 publications
5
52
0
Order By: Relevance
“…All these recent studies Jarvis, 2001, 2003;Palo et al, 2005;Chshyolkova et al, 2006) consider the stratospheric dynamics during the Antarctic winter and spring seasons, including periods of major stratospheric warmings. Yet, although similar planetary wave signatures are revealed in the COSMIC data, they are for a period when no major stratospheric warming event was registered and for a season when planetary wave activity should be negligible in the Southern Hemisphere (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All these recent studies Jarvis, 2001, 2003;Palo et al, 2005;Chshyolkova et al, 2006) consider the stratospheric dynamics during the Antarctic winter and spring seasons, including periods of major stratospheric warmings. Yet, although similar planetary wave signatures are revealed in the COSMIC data, they are for a period when no major stratospheric warming event was registered and for a season when planetary wave activity should be negligible in the Southern Hemisphere (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the wave 2 had a traveling component similar to that of wave 1, but did not have a stationary wave component. Palo et al (2005) examined the planetary wave dynamics prior to the major stratospheric warming in the winter of 2002 in the Southern Hemisphere employing SABER temperature data. They started from the premise that wave forcing plays a key role in the preconditioning of the atmosphere prior to stratospheric warming and examined the wave interaction between eastward-propagating waves with a period of 10 days, quasi-stationary waves and the zonal mean atmospheric state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPWs (Forbes et al, 2002) or some of the normal modes (Wu et al, 1994;Talaat et al, 2002;Palo et al, 2005;Azeem et al, 2005). Recently however, Pancheva et al (2008b) have suggested a data analysis method where all types of planetary wave (stationary, zonally travelling and zonally symmetric) with zonal wavenumbers up to 3 have been simultaneously extracted from the UKMO data.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the global stratosphere data like UK Met Office (UKMO) assimilated fields (Swinbank and Ortland, 2003) or the National Centre for Environmental Prediction (NCEP) reanalysis data (Randel, 1992) provided observational evidence for interactions between the zonally propagating planetary waves, quasistationary planetary waves and the zonal mean flow (Krüger et al, 2005;Pancheva et al, 2007Pancheva et al, , 2008a. The satellite measurements as those of the HRDI and WINDII instruments onboard the UARS satellite and particularly recent measurements of the SABER and TIDI instruments onboard the TIMED satellite were employed to explore not only the temporal behavior and spatial structures of the planetary waves from lower stratosphere to the lower thermosphere (Wang et al, 2000;Forbes et al, 2002) but the coupling processes as well (Palo et al, 2005;Merzlyakov and Pancheva, 2007).…”
Section: Introductionmentioning
confidence: 99%